THE FORMATION OF THE STATE OF THE COLLECTIVE UNCONSCIOUS IN THE CONSCIOUSNESS OF YOUTH IN THE CONTEXT OF THE DIGITAL SPACE - Mambetnazarova, Mexribanu Tolibaevna (SCIENCE and SOCIETY, 2026)
The article examines the socio-psychological characteristics of the formation of mass unconsciousness among youth in the digital environment, focusing on the influence of social networks and algorithmic content on critical thinking and decision-making.